The Relationship Between Bureaucratic School Structures and Teacher Self-Efficacy - Kilinç, Ali; Koşar, Serkan; Er, Emre; Öğdem, Zeki (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
The purpose of this study was to examine the relationship between bureaucratic school structures and teachers’ self-efficacy. Participants included 252 teachers from 15 primary schools in Ankara, Turkey. Mean, standard deviation, correlation, and regression analyses were conducted. Results indicated that bureaucratic school structures and teacher self-efficacy were positively and significantly correlated and a bureaucratic school structure was a significant indicator of teacher self-efficacy. The results of the study are discussed with a focus on improving teacher self-efficacy.